Gas in the portal vein Is it still a fatal prognostic sign? About three clinical cases - Acevedo, Carlos; Suc, Bertrand; Mandirola, Fernando (Cirugía del Uruguay, 2000)
The radiologic finding of hepatic portal vein gas (HPVG) is unfrequent. We present three cases in which the finding of this sign led to the diagnosis of ischemic necrosis of the colon, with favorable outcome in two patients. In arder to rule out mesenteric ischemia, a CT sean might be performed in al/ patients with vascular risk and abdominal pain in which the cause remains unclear. lf HPVG is found, urgent laparoscopic or laparotomic explora/ion is mandatory,